2003
DOI: 10.1111/j.1752-0606.2003.tb00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Nontraditional Couples: Validity of the Marital Satisfaction Inventory‐revised With Gay, Lesbian, and Cohabiting Heterosexual Couples

Abstract: Thirty-one gay male couples and 28 lesbian couples were compared with 36 cohabiting heterosexual couples using the Marital Satisfaction Inventory-Revised (MSI-R), a multidimensional measure of relationship functioning intended for use with both traditional and nontraditional couples. Analyses of scales' internal consistency and factor structure supported the construct validity of this measure with nontraditional couples. Analyses of mean profiles on the MSI-R indicated that cohabiting opposite-gender and same-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 35 publications
2
41
0
5
Order By: Relevance
“…It has been reported that gay male individuals and male couples are participants in therapy in proportionally higher numbers than their heterosexual male counterparts (Haldeman 2005;Means-Christensen et al 2003). Nationally, about 32% of male couples have sought professional services and between 25 and 65% of gays have sought therapy (MeansChristensen et al 2003;Robinson and Howard-Hamilton 2000).…”
Section: Literature Reviewmentioning
confidence: 94%
See 3 more Smart Citations
“…It has been reported that gay male individuals and male couples are participants in therapy in proportionally higher numbers than their heterosexual male counterparts (Haldeman 2005;Means-Christensen et al 2003). Nationally, about 32% of male couples have sought professional services and between 25 and 65% of gays have sought therapy (MeansChristensen et al 2003;Robinson and Howard-Hamilton 2000).…”
Section: Literature Reviewmentioning
confidence: 94%
“…Instead, what seems to be the case is perhaps the opposite: gay males and gay male couples have developed effective ways of coping with each other and with the forces working against them. Members of these couples often deal with external forces like societal oppression primarily through the use of effective problem solving skills (Todoroff 1995), accessing professional mental health care providers (Haldeman 2005;Means-Christensen et al 2003;Robinson and Howard-Hamilton 2000), and also through high levels of social support (Campbell 2000). Social support primarily comes from ''families of choice'' or ''chosen families,'' which usually are composed of friends and/or family members who are selected by the couple and who function in a type of fictive kin position within their family (Ariel and McPherson 2000;Bepko and Johnson 2000;Campbell 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Couples who are not actively planning for marriage, some of whom may not be able to marry legally, have also become a focus within the MFT profession. These couples include cohabiting (e.g., Means-Christensen et al 2003) and same-sex couples (e.g., Bepko and Johnson 2000).…”
Section: Patterns Of Clinical Practicementioning
confidence: 99%